Experimental and normalized sensitivity based numerical analyses of a novel humidifier-assisted highly efficient indirect evaporative cooler. (June 2021) - Jamil, Muhammad Ahmad; Xu, Ben Bin; Dala, Laurent; Sultan, Muhammad; Jie, Lin; Shahzad, Muhammad Wakil
Abstract: Indirect evaporative cooling technology has emerged as an energy-efficient, low-cost, and sustainable alternative to conventional air conditioning systems for space cooling. This is because of its significant (40–50%) energy-saving potential compared to ventilation, vapor compression cooling, and desiccant cooling systems. The current paper presents a novel humidifier-assisted regenerative indirect evaporative cooler that eliminates the use of hydrophilic surfaces within the system and mitigates the fouling propensity and water management issues. A generic cell of the proposed system is fabricated and tested for different operating scenarios along with the uncertainty propagation analysis. Thereafter, a normalized sensitivity analysis is performed to identify the most influential parameters on the cooler performance. The experimental data shows an effective cooling performance with a temperature drop of 20 °C of outdoor air and cooling capacity of 175 watts of 1800 mm × 300 mm generic cell. The cooling coefficient of performance was calculated as 44 and maximum effectiveness of 83.82% for the proposed configuration. The sensitivity analysis reveals scaling trends of the coefficient of performance in the following order of primary air inlet temperature > primary air outlet temperature > primary air velocity and the cooler effectiveness as secondary air outlet temperature  >  primary air inlet temperature  >  primary air humidity  >  primary air outlet. Graphical abstract: Unlabelled Image